2016
DOI: 10.2967/jnumed.116.180992
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Innervation of Cold-Activated Brown and White Fat in Lean Young Adults

Abstract: Recent work in rodents has demonstrated that basal activity of the local sympathetic nervous system is critical for maintaining brown adipocyte phenotypes in classic brown adipose tissue (BAT) and white adipose tissue (WAT). Accordingly, we sought to assess the relationship between sympathetic innervation and cold-induced activation of BAT and WAT in lean young adults. Methods: Twenty adult lean normal subjects (10 women and 10 men; mean age 6 SD, 23.3 6 3.8 y; body mass index, 23.7 6 2.5 kg/m 2 ) underwent 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
(64 reference statements)
5
30
1
Order By: Relevance
“…In contrast, the change in skin temperature of a point on the sternum, which lacks BAT deposits, was negatively associated with change in energy expenditure. The positive relationship between ΔSCV and energy expenditure during cold exposure is consistent with previous investigations (Chen et al, ; Muzik et al, ; van der Lans et al, ; van Marken Licthenbelt et al, ; Yoneshiro et al, ). Interestingly, participants who experienced an increase in SCV temperature had a mean % ΔEE of +1.41%, while participants who experienced a decrease in SCV temperature had a mean % ΔEE of −6.49%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the change in skin temperature of a point on the sternum, which lacks BAT deposits, was negatively associated with change in energy expenditure. The positive relationship between ΔSCV and energy expenditure during cold exposure is consistent with previous investigations (Chen et al, ; Muzik et al, ; van der Lans et al, ; van Marken Licthenbelt et al, ; Yoneshiro et al, ). Interestingly, participants who experienced an increase in SCV temperature had a mean % ΔEE of +1.41%, while participants who experienced a decrease in SCV temperature had a mean % ΔEE of −6.49%.…”
Section: Discussionsupporting
confidence: 90%
“…The study detected a significant increase in RQ after cooling in women but not men (see Tables and ). A similar pattern was detected by Hadi et al () after immersing subjects' hands in 5°C water for 20 minute; however, most investigations of NST report no change in RQ (Celi et al, ; Hanssen et al, ; Muzik et al, ; Peterson et al, ; Stelly, ; U Din et al, ). An increase in RQ among women may represent a shift toward utilizing carbohydrates as a metabolic substrate for thermogenesis.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have shown that human BAT activation is related to an increase in the blood flow in BAT . Based on these results, the present study postulates that the increase in BAT activation (blood flow) could result in a redistribution of the blood in the peripheral part of the body during a cold stimulus in order to generate heat, as BAT is highly irrigated .…”
Section: Discussionsupporting
confidence: 57%
“…1). Other studies have demonstrated increased activity of sympathetic nerves in iWAT and BAT after cold stimulus 34,35 and upon central nervous system activation such as direct administration of FGF21 peptide in the brain 36 or via local optogenetic activation of sympathetic fibers 37 . The idea that communication occurs between WAT and BAT in both directions has also been previously described.…”
Section: Discussionmentioning
confidence: 99%